AN ANALYSIS OF THE MANAGEMENT OF POOR STUDENT ASSISTANCE TO IMPROVING LEARNING ACHIEVEMENT. - Rambat Nur Sasongko & Ramadita Fetrianggi (International Journal of Research Science and Management, 2020)
Poor students in Indonesia receive financial assistance. This financial assistance is called poor student assistance (PSA). The assistance is intended to keep children learning at school, not drop out, and can improve learning achievement. Unfortunately in some areas, this assistance has been mismanaged. Such as not on target who get help and not used for the benefit of improving learning. This study aims to analyze the management of poor student assistance towards improving the quality of learning. The study used a descriptive method with a survey approach. The study population was students who obtained PSA at various school levels in the city of Bengkulu, Bengkulu province, Indonesia. Samples were taken randomly, based on school and class strata. Data collection techniques with closed and open questionnaires, and documentation studies. Data were analyzed with descriptive and inferential statistics. The results showed that PSA management was not yet fully effective. But in general the PSA program is very positive for students to be able to stay in school. There are still poor management components of PSA, such as planning, coordination, implementation, monitoring and evaluation, and follow-up is still not good. The PSA program has a positive impact on students who get, but it is less positive on improving student learning achievement. Suggestions to the government that the PSA program can be managed effectively, it requires coordination with the school.